Assessing telephone-delivered cognitive–behavioural therapy (CBT) and web-delivered CBT versus treatment as usual in irritable bowel syndrome (ACTIB): a multicentre randomised trial. Issue 9 (10th April 2019) - Everitt, Hazel Anne; Landau, Sabine; O'Reilly, Gilly; Sibelli, Alice; Hughes, Stephanie; Windgassen, Sula; Holland, Rachel; Little, Paul; McCrone, Paul; Bishop, Felicity; Goldsmith, Kimberley; Coleman, Nicholas; et al.
Abstract : Objective: To evaluate the clinical effectiveness of two modes of cognitive–behavioural therapy (CBT) for IBS compared with treatment as usual (TAU) in refractory IBS. Design: A three-arm randomised controlled trial assessing telephone-delivered CBT (TCBT), web-based CBT (WCBT) with minimal therapist support, and TAU. Blinding participants and therapists was not possible. Chief investigator, assessors and statisticians were blinded. Participants were adults with refractory IBS (clinically significant symptoms for ≥12 months despite first-line therapies), recruited by letter and opportunistically from 74 general practices and three gastroenterology centres in London and South of England between May 2014 to March 2016. Co-primary outcomes were IBS Symptom Severity Score (IBS-SSS) and Work and Social Adjustment Scale (WSAS) at 12 months. Results: 558/1452 (38.4%) patients screened for eligibility were randomised: 76% female: 91% white: mean age 43 years. (391/558) 70.1% completed 12 months of follow-up. Primary outcomes: Compared with TAU (IBS-SSS 205.6 at 12 months), IBS-SSS was 61.6 (95% CI 33.8 to 89.5) points lower (p<0.001) in TCBT and 35.2 (95% CI 12.6 to 57.8) points lower (p=0.002) in WCBT at 12 months. Compared with TAU (WSAS score 10.8 at 12 months) WSAS was 3.5 (95% CI 1.9 to 5.1) points lower (p<0.001) in TCBT and 3.0 (95% CI 1.3 to 4.6) points lower (p=0.001) in WCBT. All secondary outcomes showed significantly greater improvement (p≤0.002) in CBT arms compared with TAU. There were no serious adverse reactions to treatment. Conclusion: Both CBT interventions were superior to TAU up to 12 months of follow-up. Trial registration number: ISRCTN44427879 .